Contemporary Projects of Thinking Investigation and Teaching How to Think - Duoblienė, Lilija (Acta Paedagogica Vilnensia, 2001)
Litbuanian system of education is based on teaching how to know more information and does not care how to make our thinking better. Teaching of thinking is a very important problem, but we do not have any series research work on this theme. On the contrary, in foreign scientific literature where there are a lot of investigations and suggestions about teaching of thinking. The main task of this article is to investigate teaching of thinking: different definitions of good thinking, model, conditions to teach it. It was done by using literature research method. Various conceptions about good thinking were founded: critical, reflective, reasonable, creative, higher-order, complecitive thinking. All of them have similar features: clear, logical, directed, contextual, use experience and obvious examples, ordered, can implicate and lead to consequences. Investigators are divided according to their philosophical or psychological position. Therefore, criticism and reflectiveness are defined as fundamental for good thinking. Educators suggest teaching how to think critically and reflectively during different lectures or to teach it at philosophy lessons. Teaching of better thinking is recommended not only for students, but also for teachers.